2018
DOI: 10.1007/s11255-018-1888-8
|View full text |Cite
|
Sign up to set email alerts
|

Exploring sex-specific differences in the presentation and outcomes of ANCA-associated vasculitis: a nationwide registry-based cohort study

Abstract: Male sex is associated with increased risk of ESRD across all histological classes of ANCA-GN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 12 publications
0
23
11
Order By: Relevance
“…Although deteriorated GFR is a known predictor of ESRD [ 2 5 , 21 23 ], there are conflicting results of the effect of MPO (or p-ANCA)-positivity on the renal outcome [ 3 , 5 , 16 , 21 , 23 , 25 ]. Recent studies from Norway also related female gender to favorable renal survival in AAV [ 27 , 28 ]. The reasons for this gender-specific difference regarding ESRD risk remained elusive in our cohort and further research is required respecting this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Although deteriorated GFR is a known predictor of ESRD [ 2 5 , 21 23 ], there are conflicting results of the effect of MPO (or p-ANCA)-positivity on the renal outcome [ 3 , 5 , 16 , 21 , 23 , 25 ]. Recent studies from Norway also related female gender to favorable renal survival in AAV [ 27 , 28 ]. The reasons for this gender-specific difference regarding ESRD risk remained elusive in our cohort and further research is required respecting this issue.…”
Section: Discussionmentioning
confidence: 99%
“…However, few data exist about sex-specific differences in AAV glomerulonephritis (ANCA-GN) outcomes. A recent study 14 demonstrated that males have a significantly higher risk of progression to ESKD, particularly in those with crescentic Berden class. A limitation of this study was the lack of personalised treatment data to allow modelling for association with renal outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike most autoimmune diseases, AAV displays a slight male predominance 11 , 12 , with the male: female ratio reported as 1.0:0.9 13 . Proteinase 3 (PR3)-ANCA is more prevalent than myeloperoxidase (MPO)-ANCA in males 14 . However, few data exist about sex-specific differences in AAV glomerulonephritis (ANCA-GN) outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, sustained chronic kidney disease stage 5 is increasingly recognised as part of the ESKD de nition, but was not included in our study (in line with the Norwegian study). We chose to use identical inclusion criteria and de nitions to Bjørneklett et al 14 to enable accurate validation. Similarly, only biopsy proven cases were included, which results in selection bias towards more severe cases.…”
Section: Discussionmentioning
confidence: 99%
“…Participants of this retrospective cohort study were either previously recruited to the national Irish Rare Kidney Disease (RKD) Registry and Biobank 15 , or followed by the vasculitis team at the Royal Free Hospital (RFH), London (United Kingdom (U.K.)), between 2012-2020. Participants had to have a prior diagnosis of AAV pauci-immune glomerulonephritis, con rmed on kidney biopsy, with at least three glomeruli 5,14 , and positive serology for anti-MPO or -PR3 antibodies. Patients with secondary vasculitis or dual anti-glomerular basement membrane disease were excluded, in accordance with the European Medicines Agency algorithm 16 .…”
Section: Study Participantsmentioning
confidence: 99%